2020
DOI: 10.3390/polym12122985
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Mechanism of Silkworm Seroins

Abstract: Seroin 1 and seroin 2 are abundant in silkworm cocoon silk and show strong antibacterial activities, and thus are thought to protect cocoon silk from damage by bacteria. In this study, we characterized the expression pattern of silkworm seroin 3, and found that seroin 3 is synthesized in the female ovary and secreted into egg to play its roles. After being infected, seroin 1, 2, and 3 were significantly up-regulated in the silkworm. We synthesized the full-length protein of seroin 1, 2, and 3 and their N/C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Noticeably, the SF/FG composites also exhibit moderate antibacterial activity, with a bacterial inactivation rate of 9.63%, which can be attributed to the antimicrobial activity of the abundant seroin in silk. [38] The above results reveal that the synergetic antibacterial activity of ZnO NPs and SF microspheres is what endows the ZSF/FG composites with remarkable antibacterial efficacy.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Noticeably, the SF/FG composites also exhibit moderate antibacterial activity, with a bacterial inactivation rate of 9.63%, which can be attributed to the antimicrobial activity of the abundant seroin in silk. [38] The above results reveal that the synergetic antibacterial activity of ZnO NPs and SF microspheres is what endows the ZSF/FG composites with remarkable antibacterial efficacy.…”
Section: Resultsmentioning
confidence: 75%
“…However, the direct incorporation of ZnO NPs into FG achieved an undesirable lethality (less than 85.2%), as shown in Figure S6, which may be attributed to the antioxidant activity of FG. Noticeably, the SF/FG composites also exhibit moderate antibacterial activity, with a bacterial inactivation rate of 9.63%, which can be attributed to the antimicrobial activity of the abundant seroin in silk [38] . The above results reveal that the synergetic antibacterial activity of ZnO NPs and SF microspheres is what endows the ZSF/FG composites with remarkable antibacterial efficacy.…”
Section: Resultsmentioning
confidence: 76%
“…While the antimicrobial properties of seroin 1 and 2 are well known, seroin 3 has only recently been studied. A recent study showed that seroin 1, seroin 1-N, and seroin 1-C had no bacteriostatic effect on Escherichia coli , seroin 2 had better antibacterial activity, and seroin 3 had stronger bacteriostatic activity against Gram-positive bacteria than against Gram-negative strains ( Zhu et al, 2020 ).…”
Section: Natural Products With Antibacterial Activitymentioning
confidence: 99%
“…First, the cocoons, which are immobile and non-metabolizing entities, must be protected from infection and ensuing decay. This explains the presence in their composition of defense antimicrobial proteins [ 98 , 99 , 100 , 101 ]. Second, the cocoons are themselves responsible for the survival of the species by protecting the pupae from pathogens, predators, sunlight, humidity, and heat.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of non-protein matter in B. mori silk cocoon is traditionally reported [ 103 , 104 ] as 1.2–1.6% carbohydrates, ∼0.7% inorganic matter, 0.4–0.8% wax matter, and ∼0.2% pigments. The rest consists of the two major proteins in the silk thread, fibroin, and sericin, which are accompanied by much lower amounts of other proteins having either identifiable defense functions (enzymes, seroins, protease inhibitors) or other roles yet to be determined [ 99 , 100 , 101 , 104 ]. Regarding BMSS itself, the number and the distribution of constituting peptidoid units are still disputed.…”
Section: Discussionmentioning
confidence: 99%